Management of Avascular necrosis of femur head with the help of Arthrox- A case study. - Mahajan, Deepak; Naram, Smita; Parekh, Hemang (British Journal of Healthcare and Medical Research, 2021)
Osteonecrosis or bone infarction, which is a death of bone tissue due to interruption of the blood supply, is also called as avascular necrosis (AVN) and the most commonly affected bone is femur. Line of treatment may include some medication, bed rest, stretching, physiotherapy and surgery. As many as 20,000 people develop AVN each year, most ages between 20 and 50 commonest being in male then in female. Due to lack of promising results patient search for alternative therapies and remedies. We can apply basic principles of Ayurveda to treat any modern disease like AVN. This disease can be correlated with Asthi majja gata vata described in the Samhitas and Asthivaha srotodushti vikaras. ). In this article a male patient diagnosed as Asthi Majja gata vata is treated with Arthrox treatment which includes Virechana, Karma Basti and Hip dhara. His symptoms were assessed by two methods: Visual Analog Scale (VAS) change in pain and Harris Hip Score. Both help to ascertain overall quality of life. The patient was also given customized herbal remedies, manufactured by Ayushakti Ayurveda. With the help of this we can avoid the surgery, we can reduce the pain and we can serve a better quality of life for the patients with avascular necrosis of femur head. The recovery in this case was promising and was worth for documentation.